PEMBELAJARAN MENULIS LAPORAN DENGAN TEKNIK KOOPERATIF TERPADU MEMBACA DAN MENULIS SMPN 1 GEBANG - Atin, Sri (Bahtera Indonesia, 2021)
This research begins with the problem faced by the teacher, namely the lack of students' ability to understand the material. This study aims to improve the ability of grade IX students at SMPN 1 Gebang Cirebon Regency in understanding Indonesian subjects in the subject of "Technology" with the subject "Writing Reports" through the application of the Integrated Reading and Writing Cooperative Technique, so that learning Indonesian becomes more enjoyable and creates creativity. The method used was Classroom Action Research (PTK) which was carried out in class IX SMPN 1 Gebang Cirebon Regency. Activities carried out in two cycles of action. The results showed that the application of the Integrated Reading and Writing Cooperative Technique could improve students' understanding in learning Indonesian "Writing Report" in class IX of SMPN 1 Gebang Cirebon